A study on alternative livelihoods of women in farming households of Baramngay Jovellar, Igbaras, Iloilo. - Estranero, Jesela E.
The study attempts to find out the alternative livelihoods of women in farming households of Barangay Jovellar, Igbaras. This study attempts to answer the following objectives: 1) to describe the various alternative livelihoods engaged in by women in barangay Jovellar; 2) to know what specific alternative livelihoods engaged in by married and unmarried adult women; 3) to know whether alternative livelihoods of women vary according to farming seasons; and 4) to understand the reason why married and unmarried adult women engaged in alternative livelihoods., Barangay Jovellar in the municipality of Igbaras Iloilo was selected for the study. Women from farming households aged 15 to 65 years old were the respondents of this study. There were 77 of them in all who were interviewed. Interview Schedule was used in gathering data. The result of the study shows that alternative livelihood as the other occupation or resources of income of women greatly influence their economic status. This is because the occupation they had or jobs they performed led them to support their household and family needs. The study revealed that alternative livelihood of women is effective in providing income generating project of the respondents.